2010
DOI: 10.1097/inf.0b013e3181e2817f
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Varicella After Implementation of Routine Childhood Varicella Vaccination in Germany

Abstract: A country-wide sentinel surveillance system was initiated in Germany after

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 5 publications
2
22
0
Order By: Relevance
“…7,8,15 Our analysis showed that the burden of varicella-related disease has been reduced by about 40% overall, with an even greater decrease of about 60% in children below 5 y of age. Table 1.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…7,8,15 Our analysis showed that the burden of varicella-related disease has been reduced by about 40% overall, with an even greater decrease of about 60% in children below 5 y of age. Table 1.…”
Section: Discussionmentioning
confidence: 92%
“…7 At the same time, varicella-related complications were reduced by 81%, with the greatest decrease in age groups 0-4 and 5-9 y. 8 When the number of complicated cases in the sentinel surveillance became very low, this part of the sentinel surveillance was no longer sensitive enough to generate valid data and was stopped in March 2011. Moreover, sentinel reporting was prone to underreporting of severe varicella cases that presented directly in the hospital and that were not retrospectively reported by sentinel physicians.…”
Section: Introductionmentioning
confidence: 99%
“…Studies analysing surveillance data from the vaccination era showed a decline of varicella incidence and hospitalisations over time and with increasing vaccine uptake (Siedler and Arndt 2010; Siedler et al 2013b; Siedler and Dettmann 2014; Spackova et al 2010; Streng et al 2013). The proportion of patients with complications was higher in the pre-vaccination era (5.7 %) (Wagenpfeil et al 2004) than in the vaccination era (0.34–0.8 %) (Spackova et al 2010; Streng et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The proportion of patients with complications was higher in the pre-vaccination era (5.7 %) (Wagenpfeil et al 2004) than in the vaccination era (0.34–0.8 %) (Spackova et al 2010; Streng et al 2013). Annual incidence of varicella-related hospitalisations varied from 3.25 to 19.7 per 100,000 children depending on the data source used before routine childhood vaccination against varicella was implemented (Liese et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…A countrywide sentinel surveillance system was initiated in Germany after implementation of routine varicella vaccination. In that survey the number of reported varicella cases as well as chickenpox complications decreased by 63% and 81%, respectively, and neurologic complications accounted for only 0.03% of all cases [14]. …”
Section: Discussionmentioning
confidence: 99%